Adjunctive therapy with statins reduces residual albuminuria/proteinuria and provides further renoprotection by downregulating the angiotensin II–AT1 pathway in hypertensive nephropathy. Issue 7 (July 2017) - Zhang, Zhi; Li, Ziqiang; Cao, Kaijin; Fang, Dailong; Wang, Fazhan; Bi, Gang; Yang, Jian; He, Yingju; Wu, Jinhui; Wei, Yuquan; Song, Xiangrong
Abstract : Objectives: Blockade of the renin–angiotensin II (Ang II) system by AT1 blockers (ARBs) and angiotensin-converting enzyme inhibitors retards the progression of chronic kidney disease (CKD) by reducing albuminuria/proteinuria. However, many patients with CKD suffer from residual albuminuria/proteinuria, which is an independent risk factor for CKD progression. The aim of the current study is to investigate the effect of pitavastatin, one of the adjunctive agents to ARBs, on the reduction of albuminuria/proteinuria and further renoprotection mediated by telmisartan in spontaneously hypertensive rats. Methods and results: Forty-two-week-old spontaneously hypertensive rats were grouped randomly and received 8 weeks of treatments with vehicle, telmisartan, pitavastatin or a combination of telmisartan and pitavastatin. Both albuminuria and proteinuria were inhibited significantly in the telmisartan-treated group, but an obviously residual albuminuria was maintained. The combination treatment with telmisartan and pitavastatin displayed a more effective decrease in albuminuria and proteinuria, even to the normal level. Enhanced nephroprotection was also observed in this combination group, which was independent of the cholesterol-lowering effects. Further mechanistic studies revealed that the combination therapy greatly attenuated the expression of intrarenal Ang II and AT1, thereby decreasing the activation of TGF-β-Smad and NF-κB and inhibiting fibrosis and inflammation. Conclusion: Adjunctive therapy with pitavastatin dramatically reduced residual albuminuria/proteinuria and enhanced nephroprotection, likely by downregulating the expression of intrarenal Ang II and AT1. It could be concluded that statins might be a promising adjunctive therapeutic agent to conventional ARB treatment in hypertensive renal damage. Abstract : Supplemental Digital Content is available in the text